Prikaz knjige Julia Kuehn i Paul Smethurst (ur.): Travel Writing, Form and Empire: The Poetics and Politics of Mobility - Grgurinović, Ivona (2010)
U radu se prikazuje zbornik Travel Writing, Form and Empire: The Poetics and Politics of Mobility, urednika Julie Kuehn i Paula Smethursta, London i New York: Routledge, 2009
Projekt MZOS
HRV